High-performance permanent magnet array design by a fast genetic algorithm (GA)-based optimization for low-field portable MRI - Liang, Ting-Ou; Koh, Yan Hao; Qiu, Tie; Li, Erping; Yu, Wenwei; Huang, Shao Ying (Journal of magnetic resonance (1997), 2022)
[Display omitted] •In this paper, we present a new optimized cylindrical magnet array based on inward-outward ring configuration which has an average field strength of 101.5 mT, a longitudinal field direction, and a nearly monotonic field pattern with average inhomogeneity of 6.97 mT (an average RF bandwidth of 6.9 %) within a Field of View (FoV) of 200 mm in diameter and 125-mm long for head imaging.•It can work with gradient coils in the other two directions, or can be rotated to encode the signal by itself for imaging. For the rotation, the part that need to be rotated is designed to be light, 15 kg out of a total weight of 151 kg. Meanwhile, it is compact (616 mm wide, 480 mm long) and has a 5-Gauss range of 1840 × 1840 × 2340 mm3, allowing an operation in a small space. It has a magnetic field generation efficiency of 0.67 mT/kg, which is high among the sparse permanent magnet arrays that are designed for a FoV of 20 cm in diameter. This proposed magnet array can be a promising alternative to supply the main field and gradient fields combined for dedicated portable MRI.•The proposed magnet array supplies a high magnetic field in the axial direction that is the same as that of a superconducting-magnet system, which opens up numerous opportunities to apply the technical advancement developed for the existing MRI systems to further develop a portable MRI based on permanent magnet arrays. Lightweight and compact permanent magnet arrays (PMAs) are suitable for portable dedicated magnetic resonance imaging (MRI). It is worth exploring different PMA design possibilities and optimization methods with an adequate balance between weight, size, and performance, in addition to Halbach arrays and C-shaped/H-shaped magnets which are widely used. In this paper, the design and optimization of a sparse high-performance inward-outward ring-pair PMA consisting of magnet cuboids is presented for portable imaging of the brain. The design is lightweight (151kg) and compact (inner bore diameter: 270mm, outer diameter: 616mm, length: 480mm, 5-Gauss range: 1840×1840×2340mm3). The optimization framework is based on the genetic algorithm with a consideration of both field properties and simulated image quality. The resulting PMA design has an average field strength of 101.5 mT and a field pattern with a built-in linear readout gradient. Subtracting the best fit to the linear gradient target resulted in a residual deviation from the target field of 0.76mT and an average linear regression coefficient of 0.85 to the linear gradient. The required radiofrequency bandwidth is 6.9% within a field of view (FoV) with a diameter of 200mm and a length of 125mm. It has a magnetic field generation efficiency of 0.67mT/kg, which is high among the sparse PMAs that were designed for an FoV with a diameter of 200mm. The field can be used to supply gradients in one direction working with gradient coils in the other two directions, or can be rotated to encode signals for imaging with axial slice selection. The encoding capability of the designed PMA was examined through the simulated reconstructed images. The force experienced by each magnet in the design was calculated, and the feasibility of a physical implementation was confirmed. The design can offer an increased field strength, and thus, an increased signal-to-noise ratio. It has a longitudinal field direction that allows the application of technologies developed for solenoidal magnets. This proposed design can be a promising alternative to supplying the main and gradient fields in combination for dedicated portable MRI. Lastly, the design is resulted from a fast genetic algorithm-based optimization in which fast magnetic field calculation was applied and high design flexibility was feasible. Within optimization iterations, image quality metrics were used for the encoding field of a magnet configuration to guide the design of the magnet array.